MAPLE SYRUP URINE DISEASE: REPORT OF TWO CASES - Mendoza Jamanca, Wendy Lizeth (2024)
Maple syrup urine disease is a congenital metabolic disorder, commonly presenting as acute neonatal encephalopathy. Case 1. A 7-day-old neonate exhibited somnolence and refusal to breastfeed, later developing respiratory failure, neurological impairment, metabolic acidosis, and death. Elevated levels of branched-chain amino acids and a confirmatory genetic test established the diagnosis. Case 2. A 10-day-old neonate was admitted with breastfeeding refusal, hypoglycemia, and seizures. Elevated branched-chain amino acids confirmed the diagnosis genetically. The patient received parenteral nutrition and a special formula, leading to progressive neurological improvement. Currently, at 2 years and 7 months, the patient remains under multidisciplinary follow-up. Conclusion. Early detection of maple syrup urine disease through neonatal screening significantly improves neurological outcomes.